DIFFERENCES IN PERCENTAGE OF CASTOR OIL ON WATER ABSORPTION AND SOFTNESS OF RABBIT ZEEMLER SKIN - Titik Anggraini; Tutik Maryati (Politek ATK Yogyakarta Press, 2023)
This study aims to evaluate the flexibility and water absorption of the skin of oil-tanned rabbits / zeemler with different percentages of castor oil. A total of 9 pieces of rabbit skin were randomly divided into 3 treatments with 3 replications. The treatment given was the percentage of castor oil (15%), medium (20%) and high (25%). Variables observed included weakness and water absorption. The data collected was analyzed by analysis of variance followed by Duncan's New Multiple Range Test. The results showed that the suppleness of oil tanned leather with the percentage of 15% and 25% castor oil was higher (P>0.05) than the percentage of 20%. The percentage of 15% castor oil resulted in a higher water absorption than the percentages of 20% and 25%. It was concluded that the quality of the zeemler rabbit skin tanned with castor oil met the Indonesian National Standard No 06-1752-1990. The use of various castor oil had no effect on the results of the Zeemler skin moisture absorption and skin elasticity tests.